Adaptation of an Evidence-Based Diabetes Management Intervention for Delivery in Community Settings: Findings From a Pilot Randomized Effectiveness Trial. (27th November 2017) - Ellis, Deborah A; Carcone, April Idalski; Naar-King, Sylvie; Rajkumar, Dixy; Palmisano, Gloria; Moltz, Kathleen
Abstract: Objective: To adapt an evidence-based intervention targeting diabetes management in adolescents with poorly controlled type 1 diabetes for use in a community setting by community health workers (CHWs) and to conduct pilot testing of the new intervention, REACH for Control (RFC). The study was conducted as a collaboration between university researchers and a federally qualified health center. Methods In a pilot effectiveness trial, feasibility and acceptability of RFC were evaluated based on participant enrollment, treatment dose, and consumer satisfaction. RFC effects on adolescent adherence, health outcomes, and quality of life were also assessed. The trial used a parallel group design. Families were randomized to 6 months of RFC plus standard medical care ( n = 26) or standard care (SC) only ( n = 24). Data were collected at baseline and 7-month posttest. A mixed-methods approach was used to analyze data. Results: Qualitative analyses suggested that caregivers viewed RFC and delivery of a home-based intervention by CHWs positively. Furthermore, adolescents who received RFC had statistically significant ( p = .05) and clinically meaningful improvements in hemoglobin A1c (HbA1c) (0.7%) and reported significant improvements in quality of life from baseline to follow-up ( p = .001). No significant changes were found for adolescents in standard medical care. However, while dose of primary intervention session delivered was acceptable, dose of follow-up sessions used for skills practice was low. Conclusions: Results provide preliminary support for RFC's acceptability and effectiveness to improve health status and quality of life when used in community settings serving high-risk, low-income families. Additional testing in a full-scale effectiveness trial appears warranted.